Hip Replacement Surgery in 14-Year-Old Girl with Factor V Deficiency: Haemostatic Treatment and Thromboprophylaxis - Mingot-Castellano, María Eva; Pérez-Núñez, Josefina; Baeza-Montañez, Lourdes (Case Reports in Hematology, 2016)
Factor V (FV) is a pivotal coagulation factor present in plasma and platelets. It plays an essential role in secondary haemostasis acting as a cofactor in the prothrombinase complex, catalysing the conversion of prothrombin to thrombin. There is little evidence on the management of mayor orthopaedic surgery in paediatric or adolescents subjects with this coagulopathy and almost no information about thromboprophylaxis in these situations. We report a case of a hip replacement in a 14-year-old girl with moderate FV deficiency (0.07 IU mL−1). As haemostatic replacement, inactivated fresh frozen plasma (FFP) was transfused at doses of 600 mL (15 mL kg−1, 45 kg weight) 2 hours before surgery and then sequential FFP infusions of 250 mL (7 mL kg−1) every 12 hours for 7 days. Plasma factor VIII, von Willebrand factor antigen, and von Willebrand ristocetin cofactor were monitored to avoid supranormal levels. Since the patient was sexually mature (Marshall and Tanner stage 5) with the hormone replacement therapy, she was immobilized and the surgery was considered as a high thrombotic risk. Thus, low molecular weight heparin was administered at doses of intermediate risk (Enoxaparin 20 mg daily, by weight) after finishing the daily infusion of plasma: 24 hours and during the 7 days after intervention. No tranexamic acid was used. No haemorrhagic or thrombotic adverse event was described.